Commentary: Reflecting the new realities of the digital age - Matt Mollgaard (Asia Pacific Network, 2007)
Three broad themes reflecting the role of the media in the digital age emerged from the Journalism Downunder journalism education conference in Auckland in December 2006. These were trepidation, confusion and celebration. The sense of trepidation relates to a fear of the unknown and unknowable: a sense that digital technologies are changing at a speed that confounds attempts to master them before they morph into new forms. Another theme was the confusion created by the new digital technologies. This confusion is related to the fetish-isation of gadgets and the growing gap between those who have always interacted with the digital world and those who have had it thrust upon them. The third theme was cautious celebration. The power, speed and usefulness of digital creation, transmission and reception opens up communication and the media to people in previously unimaginable ways. This commentary is an overview of papers presented at the conference, with some general conclusions reached about the future of journalism in the digital age. While the new digital platforms and technologies do present significant challenges to traditional journalism, they are also enabling technologies that offer opportunities to reinvigorate newsgathering. Although the future of journalism is a digital one, the core competencies of a good journalist will be as important as ever.